“Evaluación de cuatro densidades de siembra a doble hilera en el rendimiento y calidad de fruto del paprika (capsicum annuum L.) variedad papriking en el fundo Miraflores – San Martín – Perú” - Perez Acuña, Franklin (2007)
The present investigation work "Evaluation of four to sow densities to double array in the yield and quality of the fruit of the Paprika (Capsicum annum L.) variety Papriking in the 1 found Miraflores - San Martin - Peru.", sector Ahuashiyacu, to 500 m of the highway Bello Horizonte, belonging to the district of the Shilcayo Band and county of San Martín, region San Martín, valley Low May; property of the National University of San Martín - Tarapoto that had for objectives, to determine the density of appropriate siembra in the Paprika (Capsícum annum L.), cultivation to obtain better yield and the quality of fruits to obtain better yields and fruit quality; and to carry out the economic analysis of the treatments based on the relationship benefit I cost to determine the profrtability for hectare. The floor presentad the following ones characteristic: sandy textura franc, pH of 5,08, with 3,83% of M.O. (High), 15,5 ppm of available match (1 lower); O, 11 meq of interchangeable potassium (1 Lower) and Calcium + Magnesium with 4,3 meq (Half). You work with a design of Blocks Totally at random (OSCA) with four treatments (Distancings) and three blocks being the following ones: Treatment 1: 0,30 m (among plants) x 1 m (array). Witness. Treatment 2: 0,20 m (among plants) x 1 m (array). Treatment 3: 0,50 m (among plants) x 1 m (array). Treatment 4: 0,60 m (among plants) x 1 m. (array). ' Concluding that that the density of O, 60 x 1,0 m (T4), the one that 1 throw better so much yield in fresh fruit was (29 038 Kg /ha), as well as in dry fruit (5 534,4 Kg I ha), that is to say that for this variety papriking one observes that to smaller density of plants for area unit the yield has been increased, so much in fruits. As for the maximum economic benefrt for the present investigation you achievement with the distancing 0,60 x 1m (T4) with a relationship B/C 4 ,27 and the smallest relationship B/C you achievement with the distancing 0,20 x 1,0 m (T2) with a value of 1, 78; in comparison to the other treatments.